Peran Sanggar Rojolele dalam Meningkatkan Posisi Tawar Petani Melalui Penguatan Kapasitas Petani - Sulastri, Endang; Winarno, Joko; Rusdiyana, Eksa (Balai Pelatihan Pertanian Jambi, 2023)
Sanggar Rojolele is a youth group in Delanggu Village that actively speaks out on agricultural issues such as farmers' bargaining position. This research aims to analyze the role and efforts of Sanggar Rojolele in strengthening farmers' capacity and improving farmers' bargaining position. The research method used is qualitative with a case study approach. The research location is chosen purposively in Delanggu Village, Delanggu District, Klaten Regency. The informant's determination was purposive and snowball sampling. Data collection techniques were in-depth interviews, participatory observation, and documentation. Data analysis used Miles and Huberman's interactive analysis with triangulation of sources and techniques for data validity. The results showed that Sanggar Rojolele acts as a facilitator, educator, and advocate in improving learning capacity, organizational capacity, and business capacity. Sanggar Rojolele helps by providing information facilities, facilitating counseling and training activities, and assisting farmers in accessing productive resources such as agricultural technology, inputs, agricultural infrastructure, and access to market information. Sanggar Rojolele's efforts in improving bargaining position by becoming a collective marketing platform for farmers that imcreases competitiveness, and ease in reaching the market, streamline marketing activities, and protect farmers from price games.